Efflux transporters in blood-brain interfaces of the developing brain - Strazielle, Nathalie; Ghersi-Egea, Jean-François (Frontiers in Neuroscience, 2015)
The cerebral microvessel endothelium forming the blood-brain barrier (BBB) and the epithelium of the choroid plexuses forming the blood-CSF barrier (BCSFB) operate as gatekeepers for the CNS. Exposure of the vulnerable developing brain to chemical insults can have dramatic consequences for brain maturation and lead to life-long neurological diseases. The ability of blood-brain interfaces (BBIs) to efficiently protect the immature brain is therefore an important pathophysiological issue. This is also key to our understanding of drug entry into the brain of neonatal and pediatric patients. Nonspecific paracellular diffusion through BBIs is restricted early during development, but other neuroprotective properties of these interfaces differ between the developing and adult brains. This review focuses on the developmental expression and function of multispecific efflux transporters of the ABCB, ABCC, ABCG, SLC21, SLC22, and SLC15 families. These transporters play a key role in preventing brain entry of blood-borne molecules such as drugs, environmental toxicants, and endogenous metabolites, or else in increasing the clearance of potentially harmful organic ions from the brain. The limited data available for laboratory animals and human highlight transporter-specific developmental patterns of expression and function, which differ between BBIs. The BCSFB achieves an adult phenotype earlier than the BBB. Efflux transporters at the BBB appear to be regulated by various factors subsequently secreted by neural progenitors, and astrocytes during development. Their expression is also modulated by oxidative stress, inflammation, and exposure to xenobiotic inducers. A better understanding of these regulatory pathways during development, in particular the signaling pathways triggered by oxidative stress and xenobiotics, may open new opportunities to therapeutic manipulation in view to improve or restore neuroprotective functions of the BBIs in the context of perinatal injuries.